Implementasi Program Keluarga Harapan Di Desa Ciwangi Kecamatan Balubur Limbangan Kabupaten Garut - Immanuel Gok Asiniroha Hariandja; Didin Muhafidin (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
This research was conducted with the aim of understanding the implementation of the Family Hope Program (PKH) in the Ciwangi Village, Balubur Limbangan District, Garut Regency. Several issues were identified in the implementation process, causing it to not run smoothly. This was due to various factors related to policy substance, the behavior of implementers, network interaction, target group participation, and resources in the implementation in Ciwangi Village, Balubur Limbangan Subdistrict, Garut Regency. The theory used in this research is the policy implementation theory proposed by Muchlis Hamdi (2014), which consists of policy substance, the behavior of implementers, network interaction, target group participation, and resources. This research utilized a qualitative research method with data collection techniques through observation, interviews, and documentation. The informant selection technique employed was purposive sampling, with a total of 8 informants. The findings indicate that the implementation of the Family Hope Program in Ciwangi Village, Balubur Limbangan District, Garut Regency, has not fulfilled several factors crucial for the success of policy implementation. However, there are also factors that have been fully met, such as policy substance and network interaction.